Tidak Kompeten! Bagaimana Laki-Laki Memandang Perempuan dalam Game Online Valorant? - Putra Sudiana, Nyoman Agil; Sari, Ratna Permata (Jurnal Mahasiswa Komunikasi Cantrik, 2023)
Online games are an activity that male players dominate. However, Valorant is a game that is also popular with female players. This often gives rise to stereotypes among men. This research investigates female stereotypes in the online game Valorant. This research uses virtual ethnographic methods. Data collection was carried out using participant observation and in-depth interviews. Gender stereotypes believed by male players in the online game Valorant are assessed from cognitive, affective, and conative aspects. This research found that female gender stereotypes, from a cognitive aspect, are incompetent in playing, do not accept input, and have good teamwork. From the affective aspect, female players are identified as being sensitive, easily irritated, lacking confidence in their playing performance, communicating aggressively, and often saying rude things. From the conative aspect, male players always take action to ensure that female players are protected and led, tend to choose agents with a supporting role, are not competitive, and are passive in communicating.